2020
DOI: 10.5123/s1679-49742020000300004
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciais por sexo na mortalidade evitável e ganhos potenciais de esperança de vida em São Paulo, SP: um estudo transversal entre 2014 e 2016

Abstract: Objective: to estimate potential life expectancy gains and differences between males and females, if avoidable deaths from circulatory system diseases, neoplasms and external causes had been eliminated in São Paulo, SP, Brazil, in the period 2014-2016. Methods: this was a cross-sectional study using data from the Mortality Information System (SIM), and the Brazilian Institute of Geography and Statistics (IBGE), using multiple decrement tables. Results: of the 81,087 deaths from the diseases studied here, 75.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
3
0
4
Order By: Relevance
“…O mesmo foi observado em estudo na região metropolitana de Buenos Aires, com bolivianos vivendo e trabalhando em condições precárias 26 , o que favorece a maior frequência de doenças respiratórias 27 . Diversos estudos 26,28 mostram melhores condições de saúde entre as mulheres. Nossos resultados evidenciaram que os homens registraram maior proporção de causas evitáveis quando comparados às mulheres, nas duas nacionalidades estudadas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O mesmo foi observado em estudo na região metropolitana de Buenos Aires, com bolivianos vivendo e trabalhando em condições precárias 26 , o que favorece a maior frequência de doenças respiratórias 27 . Diversos estudos 26,28 mostram melhores condições de saúde entre as mulheres. Nossos resultados evidenciaram que os homens registraram maior proporção de causas evitáveis quando comparados às mulheres, nas duas nacionalidades estudadas.…”
Section: Discussionunclassified
“…Nossos resultados evidenciaram que os homens registraram maior proporção de causas evitáveis quando comparados às mulheres, nas duas nacionalidades estudadas. Resultado semelhante foi observado em estudo realizado em São Paulo 28 que avaliou mortes evitáveis por câncer, hipertensão e causas externas, com destaque para causas externas que impactam mais homens do que mulheres.…”
Section: Discussionunclassified
“…Other studies have shown that Bolivian immigrants living in São Paulo experience poor living and working conditions and often live and work in the same space 16,[23][24][25] Bolivian immigrants living in the Buenos Aires metropolitan area 26 and other studies have shown poor living and working conditions can lead to a higher frequency of respiratory diseases 27 . Various studies 26,28 show that women have better health status than men. Our findings show that the proportion of deaths from avoidable causes was higher among men in both nationalities.…”
Section: Discussionmentioning
confidence: 99%
“…Low life expectancy for males is related to "deaths for external causes" among teenagers and young adults. 2 Brazil ranks 28 th infant mortality rate with 11.0 infant deaths per 1,000 live births and ranks 24 th in deaths of children under 5 years old: 13.0 per 1,000 live births. 3 Similarly to other countries, the country suffers from a high burden of non-communicable diseases, accounting for 91% of deaths.…”
Section: Brazilian National Health Systemmentioning
confidence: 99%